2012
DOI: 10.1063/1.3686212
|View full text |Cite
|
Sign up to set email alerts
|

ZnO coated nanospring-based chemiresistors

Abstract: Chemiresistors were constructed using 3-D silica nanospring mats coated with a contiguous film of ZnO nanocrystals. Chemiresistors with an average ZnO nanocrystal radius <3 nm, or >20 nm, were found to exhibit a relative change in conductance of a factor of 50 upon exposure to a gas flow of 20% O2 and 80% N2 with ∼500 ppm of toluene and an operational temperature of 400 °C. Samples with an average ZnO nanocrystal radius of 15 nm were found to be the most responsive with a relative conductance cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…On the other hand, these devices are necessary for acquiring a fundamental understanding of corresponding physical and chemical processes triggered by surface-molecule interactions (chemisorption), as well as for interpreting the electrical transport properties of gas sensitive materials. The use of metal oxide nanocrystalline thin films, as well as other more complex nano-morphologies, as the gas sensitive layers in chemiresistors is well documented [1][2][3][4][5][6][7][8][9][10][11]. These studies demonstrated that if the dimensions of the nanostructures are comparable to the characteristic length scales of surface interactions, the sensor will be more responsive to changes in surface stoichiometry.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, these devices are necessary for acquiring a fundamental understanding of corresponding physical and chemical processes triggered by surface-molecule interactions (chemisorption), as well as for interpreting the electrical transport properties of gas sensitive materials. The use of metal oxide nanocrystalline thin films, as well as other more complex nano-morphologies, as the gas sensitive layers in chemiresistors is well documented [1][2][3][4][5][6][7][8][9][10][11]. These studies demonstrated that if the dimensions of the nanostructures are comparable to the characteristic length scales of surface interactions, the sensor will be more responsive to changes in surface stoichiometry.…”
Section: Introductionmentioning
confidence: 87%
“…The effects of chemisorption on the electrical transport properties of metal oxides is well documented [1][2][3][4][5][6][7][8][9][10][11][19][20][21][22]. In the case of ZnO 1- , where the surface is oxygen deficient, the surface readily oxidized in ambient air to obtain the ideal surface stoichiometry of ZnO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A viscous flow or fluidized bed reactor configuration is suitable for coating nanoparticles using ALD. More commonly, ALD of ZnO has been performed on 1D structures such as nanorods, nanotubes, nanofibers, and nanowires made of Si or SiO 2 [365][366][367][368][369][370][371][372], SnO 2 [373][374][375][376], TiO 2 (figure 15) [377], and Al 2 O 3 [378,379]. Alternatively, ALD of TiO 2 has been performed on ZnO nanofibers (figure 15) to produce TiO 2 -ZnO core-shell nanofibers [377].…”
Section: Core-shell Structuresmentioning
confidence: 99%
“…Synthesis methods have been reported to produce silica (SiO 2 ) nanoribbons, making these structures potential building block units for hierarchical systems. Novel synthesis of 3D silica nanosprings has expanded their applications to chemiresistors when coated with ZnO 8 or nanoparticles for diagnostic applications [9][10] .…”
Section: Introductionmentioning
confidence: 99%